Effectiveness of Picture Story Books Reading to Increase Kindness in Children Aged 5-6 Years - Giyati Retnowati; Rose Mini Agoes Salim; Airin Y Saleh (Bina Nusantara University, 2018)
This research aimed to determine the effectiveness of picture in storybook reading to increase kindness in children. This research involved 31 children aged 5-6 years; they were taken from the kindergarten in Bandung as the participants. The intervention was done by reading eight picture books in eight days. The kindness was measured using a measurement instrument created by the researcher, in the form of nine coloured cards that described the behaviour of kindness. The measurement was also done by seeing through the kindness tree and observation sheets that filled out by the teacher. The data analysis using the Wilcoxon Signed-rank test shows a significant difference in the average score of kindness (p<0,05) before and after picture storybook reading. Two weeks after the intervention, the improvement on all kindness behaviours with the post-test score is greater than pre-test score that still can be found. Observation through kindness tree and observational sheets shows the same result.